2019
DOI: 10.1021/acsbiomaterials.9b01359
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall PEGylated and Targeted Core–Shell Silica Nanoparticles Carrying Methylene Blue Photosensitizer

Abstract: Photodynamic therapy (PDT) presents an alternative noninvasive therapeutic modality for the treatment of cancer and other diseases. PDT relies on cytotoxic singlet oxygen (reactive oxygen species or ROS) that is locally generated through energy transfer between a photosensitizer (PS) and molecularly dissolved triplet oxygen. While a number of nanoparticle-based PS vehicles have been described, because of their beneficial and proven biodistribution and pharmacokinetic profiles, ultrasmall nanoparticles with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
(107 reference statements)
1
21
0
Order By: Relevance
“…[ 30,32 ] Furthermore, photobleaching studies based on previously published methods (see Supporting Information) showed that Cy5 encapsulated in aC’ dots is 2.8 times more photostable than in free form (Figure 1e). [ 33 ] Since we already showed in two separate previous studies that Al is fourfold coordinated in aC’ dots, replacing Si in the silica network, we did not repeat the same solid‐state 27 Al nuclear magnetic resonance (NMR) spectroscopy experiments on aC’ dot samples here. [ 24,25 ] Zeta potential measurements of aC’ dots showed a negative surface charge with an average of −11.9 mV as seen in Figure S2 in the Supporting Information.…”
Section: Figurementioning
confidence: 99%
“…[ 30,32 ] Furthermore, photobleaching studies based on previously published methods (see Supporting Information) showed that Cy5 encapsulated in aC’ dots is 2.8 times more photostable than in free form (Figure 1e). [ 33 ] Since we already showed in two separate previous studies that Al is fourfold coordinated in aC’ dots, replacing Si in the silica network, we did not repeat the same solid‐state 27 Al nuclear magnetic resonance (NMR) spectroscopy experiments on aC’ dot samples here. [ 24,25 ] Zeta potential measurements of aC’ dots showed a negative surface charge with an average of −11.9 mV as seen in Figure S2 in the Supporting Information.…”
Section: Figurementioning
confidence: 99%
“…Indeed, encapsulation should lead to the administration of the PS in a monomeric form without loss of activity. PS such as m-THPC [ 164 ], hypocrellin B [ 165 ], protoporphyrin IX (PpIX) [ 166 ], and methylene blue (MB) [ 167 ] have been encapsulated in silica nanoparticles (covalent or non-covalent), due to the EPR effect of silica nanoparticles for tumor tissues. PpIX silica nanoparticles have been investigated for effective use in PDT in vitro and in vivo models, in order to improve the role of biological factors in photodamage.…”
Section: Phototherapymentioning
confidence: 99%
“…Kohle et al investigated the effect of the position of the PS in silica nanoparticles. Two types of ultrasmall poly(ethylene glycol)-coated (PEGylated) fluorescent core–shell silica nanoparticles with methylene blue derivate (MB2) were synthesized [ 167 ]. In Design 1, MB2 was encapsulated into the matrix of the silica core, while MB2 was grafted onto the silica core surface in between chains of the sterically stabilizing PEG corona in Design 2.…”
Section: Phototherapymentioning
confidence: 99%
“…For this type II photosensitized oxygenation reaction, PDT efficiency is closely relied on the generation ratio of singlet oxygen molecule, whose low intra-tumoral yield is a major limitation for traditional and available photosensitizers [12][13][14] with requirements of high absorption coefficient [4,15] and monomer state of these lipophilic dyes without dimeric aggregation [16][17][18]. Many efforts are devoted to increase generation efficiencies of singlet oxygen molecules through promoting intersystem crossing processes by spin coupling of heavy atom effect [19][20][21][22][23], optimizing state energy levels through fine-tuned absorption wavelengths [20,22] or employing Förster resonance energy transfer pairs with photoinduced charge transfer [24][25][26]. Structural modifications [22] or sulfur substitutions of carbonyl thionaphathalimides at 2-and 6-positions [20] endow remarkable fluorescence quenching and tremendous enhancement in the rate constant of intersystem crossing, due to the significant increase of spin-orbit coupling constant and decrease of singlet-triplet energy gap [20,22].…”
Section: Introductionmentioning
confidence: 99%
“…These processes are promoted in hybrid photosensitizers, where energy and charge transformations between quantum dots (CdTe [24] or Ag [25]) and MB are employed to significantly increase the production efficiencies of singlet oxygen [24]. Recently, MB molecules are combined in cardiolipin monolayer systems [28], C' dots of silica core [23] and cucurbituril [29] to diminish π stacking-induced selfaggregation and avoid the reductive process of MB during its delivery to cancer cells. MB molecules in the triplet excited states are also protected to live with long life inside these capsules, which results in the promotion of triplet-triplet energy transfer between MB and O 2 molecules to yield singlet oxygen, exceeding performances of single MB molecules.…”
Section: Introductionmentioning
confidence: 99%